Crosstalk between cancer and immune cells: Role of tumor‐associated macrophages in the tumor microenvironment. (20th June 2019) - Wang, Jing; Li, Danyang; Cang, Huaixing; Guo, Bo
Abstract: Tumor microenvironment is a complex system that contains multiple cells and cytokines. Among the multiple immune cells, macrophage is particularly abundant and plays an important role throughout the tumor progression process, namely, tumor‐associated macrophage (TAM) in this special tumor microenvironment. Many kinds of cytokines from TAMs and other immune cells in tumor niche are involved in the linkage of inflammation, immunity and tumorigenesis. Inflammatory responses induced by TAMs are crucial to tumor development of different stages. This review highlights the critical role of TAMs in the linkage of inflammation, immunity, and cancer. It outlines the molecules of inflammatory cytokines, chemokines, and growth factors mainly from TAMs in tumor microenvironment and their functions in tumor development during the major issues of angiogenesis, chronic inflammation, and immune suppression. Additionally, the signaling pathways involved in tumor progression and the crosstalk between them are also summarized. Abstract : This review outlines the molecules of inflammatory cytokines, chemokines, and growth factors mainly from tumor‐associated macrophages (TAMs) in tumor microenvironment and their functions in tumor development during the main stages of angiogenesis, chronic inflammation and immune suppression. The signaling pathways involved in tumor progression and the crosstalk between them are outlined and highlights the critical role of TAMs in the linkage of inflammation, immunity, and cancer.